Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3174165
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Interruptibility in the Office

Abstract: Knowledge workers experience many interruptions during their work day. Especially when they happen at inopportune moments, interruptions can incur high costs, cause time loss and frustration. Knowing a person's interruptibility allows optimizing the timing of interruptions and minimize disruption. Recent advances in technology provide the opportunity to collect a wide variety of data on knowledge workers to predict interruptibility. While prior work predominantly examined interruptibility based on a single dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 71 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…All our participants were male and working in Spain, and although we do not suspect significant regional differences, they cannot be ruled out. Furthermore, a sample size of 13 participants is not very large, though not particularily low compared to other studies in software engineering (e.g., [26,44]). Given that we recruited both experienced and novice developers from several sources (universities and an international Python conference), we are confident to have mitigated this issue as far as possible.…”
Section: Threats To Validitymentioning
confidence: 94%
“…All our participants were male and working in Spain, and although we do not suspect significant regional differences, they cannot be ruled out. Furthermore, a sample size of 13 participants is not very large, though not particularily low compared to other studies in software engineering (e.g., [26,44]). Given that we recruited both experienced and novice developers from several sources (universities and an international Python conference), we are confident to have mitigated this issue as far as possible.…”
Section: Threats To Validitymentioning
confidence: 94%
“…Such measures could be considered in a potential early warning system as physiological indicators to measure autonomic nervous system activity to measure stress-related disturbances (i.e., interruptions) during task performance ( Stangl and Riedl, 2022a , 2022c ). Indeed, empirical research showed that a combination of biometric data together with computer interaction data can predict with high accuracy the interruptibility of software developers at a given moment to avoid inappropriate moments for interruptions ( Züger and Fritz, 2015 ; Züger et al, 2018 ). Another conceivable approach to extending the taxonomy is third-party evaluation.…”
Section: Review Results and Research Agendamentioning
confidence: 99%
“…This chain is composed by stages of preparation, diversion, resumption and recovery that result in time away from an ongoing task. Since interruptions can have a large impact on the focus and productivity of office workers, several studies have examined the prediction of interruptibility-the availability for interruptions-using a variety of features, including computer interaction and biometrics [46,47,48,49,16,50]. Most of these studies were again conducted for small and controlled tasks over shorter periods of time.…”
Section: Focusmentioning
confidence: 99%